The Death of Dionysus and Ethical Dualism: On Olympiodorus’ Anthropogony and Neoplatonic Depictions of the Manichaean Cosmos - Blaž Božič (Keria: Studia Latina et Graeca)
The version of anthropogony presented in Olympiodorus’ interpretation of Socrates’ philosophical argument against suicide (In Phaed. 1.3.3.–14) suggests two important questions: about the role of ethical dualism and original sin in pagan religion and philosophy on the one hand, and about the extent of Olympiodorus’ innovativeness on the other. I argue that Olympiodorus’ time foregrounded ethical dualism as a major concern in allegorical interpretations of Dionysus’ death by dismemberment, and that certain antecedents for a dualistic view might have existed (e.g. in the theological concepts of Orphic religions). Although any attempt to establish historical connections is bound to be speculative, some sources indicate that the specific link of Dionysus’ death with ethical dualism is not necessarily an innovation contributed in its entirety by Olympiodorus. I derive my main argument from a reference by Alexander of Lycopolis, who mentions that some of the Manichaeans used similar metaphors to describe the structure of the cosmos, which is based in their teachings on an ethical conflict.